Função social como princípio limitador da propriedade industrial de variedades vegetais : o caso Monsanto - Hein, Amanda Rosales Gonçalves (2014)
This paper develops a critical-legal examination on the subject of industrial property protection of plant varieties in the context of agricultural biotechnology. From the design of the context of legal, regulatory and constitutional protection of industrial property rights for plant varieties, the study aims to answer which are the limits of protection of the patents on genetically modified seeds process and if it is applicable the law of patent exhaustion in the case of transgenic soybean Roundup Ready® due to its technology self-replication nature. From the analysis of the case Monsanto v. Bowman judged by the U.S. Supreme Court, and made the necessary caveats regarding the legal system in the field of industrial property in Brazil, the work investigates whether the application - or not - of the doctrine of exhaustion of patent rights, depending on the specific case, is intrinsically related to the very social function of intellectual property, which in this work is considered as a limiting principle of the exclusive right that allows, ultimately, the reconciliation of fundamental rights in collision.